ETV4 promotes pancreatic ductal adenocarcinoma metastasis through activation of the CXCL13/CXCR5 signaling axis. (1st January 2022) - Gao, Xiaoliang; Jiang, Mingzuo; chu, Yi; Han, Yuying; Jin, Yirong; Zhang, Wenyao; Wang, Weijie; Yang, Suzhen; Li, Wenjiao; Fan, Ahui; Cao, Jiayi; Wang, Jiayao; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) has the highest fatality rate of any solid tumor, with a five-year survival rate of only 10% in the USA. PDAC is characterized by early metastasis. More than 50% of patients present with distant metastases at the time of diagnosis, and the majority of patients will develop metastasis within 4 years after tumor resection. Despite extensive studies, the molecular mechanisms underlying PDAC metastasis remain unclear. The polyoma enhancer activator protein (PEA3) subfamily was reported to play a vital role in the initiation and progression of multiple tumors. Herein, we found that ETS variant 4 (ETV4) was highly expressed in PDAC tissues and associated with poor survival. Univariate and multivariate analyses revealed that ETV4 expression was an independent prognostic factor for patient survival. Further experiments showed that ETV4 overexpression promoted PDAC invasion and metastasis both in vitro and in vivo. For the first time, we demonstrated that, mechanistically, ETV4 increased CXCR5 expression by directly binding to the CXCR5 promoter region. Knockdown of CXCR5 significantly reversed ETV4-mediated PDAC migration and invasion, while CXCR5 overexpression exerted the opposite effects. Intriguingly, we found that CXCL13, a specific ligand of CXCR5, increased ETV4 expression and promoted PDAC invasion and metastasis by activating the ERK1/2 pathway. ETV4 knockdown significantly abrogated the enhanced migratory and invasive abilities induced by the CXCL13/CXCR5 axis. In addition, a CXCR5 neutralizing antibody disrupted the CXCL13/ETV4/CXCR5 positive feedback loop and inhibited cell migration and invasion. Overall, in this study, we demonstrated that ETV4 plays a vital role in PDAC metastasis and defined a novel CXCL13/ETV4/CXCR5 positive feedback loop. Targeting this pathway has implications for potential therapeutic strategies for PDAC treatment. Highlights: ETV4 was highly expressed in PDAC tissues and associated with poor survival. ETV4 overexpression promoted PDAC invasion and metastasis both in vitro and in vivo. ETV4 transcriptionally activated CXCR5 expression by directly binding with its promoter region. CXCL13 increased ETV4 expression and promoted PDAC invasion and metastasis by activating the ERK1/2 pathway. CXCR5 neutralizing antibody disrupted the CXCL13/ETV4/CXCR5 positive feedback loop and inhibited cell migration and invasion.